The development of Libyan foreign trade and its most important challenges during the period (2015 - 2024) - ALHOUSH, YOSEF (Sharwes Scientific Journal, 2025)
Foreign trade plays a significant role in the economies of countries, impacting the balance of payments and gross domestic product (GDP), and consequently, economic growth. This study aimed to analyze Libyan foreign trade, examining the development of exports, imports, and the trade balance during the period (2015 - 2024). It relied on an analytical approach to study and analyze the development of the volume of total exports and imports, as well as their commodity and geographic structure                                               The study then examined the direction of trade exchanges and Libya's most important trading partners. The study concluded several results, the most important of which is that Libya's trade balance is primarily based on crude oil exports, which are affected by external economic variables, which are considered one of the most important challenges facing Libyan foreign trade. It is also affected by internal variables, such as the closure of oil fields, which leads to a decrease in crude oil production and its impact on export volume, in addition to the weakness of exports outside the oil sector